English literacy among Malaysian first graders: boys' achievement relative to girls - Mohd. Asraf, Ratnawati; Abdullah, Hazlina (Asian E F L Journal Press, 2016)
In the past few decades, data from numerous countries such as the United Kingdom, Canada, Australia, the Philippines, Thailand, and Malaysia show that many boys are not performing well on a range of educational achievement measures such as literacy, and that the gap between boys' and girls' performance has increased over time. This paper discusses the results of a study that sought to determine the English literacy performance of Malaysian first graders in English. Using one of the states in the country as a case study, English literacy performance data on approximately 85,000 students from grade 1 were obtained. Teachers’ views were also sought through focus group interviews and journal entries. The results show that girls outperformed boys on all English literacy constructs.